FEATURES OF SOCIO-PHILOSOPHICAL VIEWS ON THE DEVELOPMENT OF WOMEN’S ENTREPRENEURSHIP (Scientific journal of the Fergana State University, 2024)
The scientific article provides a scientific and philosophical analysis of the importance of national and universal values of the development of women’s entrepreneurship in foreign countries, opportunities for Uzbekistan to gain experience in the development of women’s entrepreneurship. The concept of “women’s entrepreneurship” is included in a number of dynamic, variable categories. The starting point is the realization that women’s entrepreneurship is a set that includes industries that generate new professions, all the elements that make up the overall system of entrepreneurship.